Study on the Chemical Constituents and Anti-Migraine Activity of Supercritical CO2 Extracts of Zanthoxylum schinifolium - Yuan, Ruifang; Shi, Yunzhen; Zhang, Jinming; Hu, Qi; Wei, Xichuan; Luo, Chuanhong; Wu, Yi; Yang, Jinhui; Yang, Ming; Wang, Fang; Zheng, Chuan; Zhang, Dingkun (Frontiers in Pharmacology, 2021)
Background:Zanthoxylum schinifolium is a common herbal medicine in Southwest China. It is also a condiment commonly used in many families. In Chinese folk medicine, Z. schinifolium is considered to have the effect of relieving migraine, but there is no modern evidence on its anti-migraine mechanism. Objective: The aim of this study was to investigate the chemical constituents of the supercritical carbon dioxide extracts of Z. schinifolium (CO2-ZSE) and its effects on migraine animals. Materials and Methods: Supercritical CO2 extraction technology was applied to extract the dried fruit of Z. schinifolium, and the chemical components were determined by gas chromatography–mass spectrometry (GC-MS). Two migraine animal models were established by subcutaneous injection of nitroglycerin (NTG) and reserpine, respectively, to further evaluate the therapeutic effect of CO2-ZSE and explore its mechanism. On the basis of the experimental results, the therapeutic effects of linalool in different dosages and different ways of administration on NTG-induced migraine rats have been further investigated. Results: About 125 peaks were detected in CO2-ZSE, and the relative content of linalool was 74.16%. CO2-ZSE decreased the number of head-scratching significantly and the levels of serum nitric oxide (NO), endothelin-1 (ET-1), calcitonin gene–related peptide (CGRP), interleukin-1β (IL-1β), nuclear factor kappa B (NF-κB) p65, and inhibitor of kappa B alpha (IκBα), and increased the level of 5-hydroxytryptamine (5-HT). Linalool has the potential to reduce the frequency of scratching the head and the expressions of NO, ET-1, and CGRP in NTG-induced migraine rats. Conclusion: CO2-ZSE has a definite therapeutic effect on migraine by affecting the expression of vasomotor factors and the inflammatory pathway. Linalool has been proven to be the main effective substance against migraine. These findings provide scientific basis for the development of effective and simple migraine therapy.